The perception of individuals with low back pain regarding reassuring information: Insights based on physiotherapists messages - Ron Shavit; Talma Kushnir; Yaniv Nudelman; Shmuel Springer (PLoS ONE, 2025)
Background Clinical guidelines for the management of low back pain (LBP) emphasize the importance of reassuring patients, as this reduces concern and increases confidence in recovery. Although physiotherapists (PTs) often use reassurance strategies, the perception of the different reassuring messages remains unclear. Objective To investigate perceptions of confidence of different reassurance messages delivered by PTs to people with LBP. Methods A survey was conducted among 544 participants with LBP. The survey included 21 reassuring messages divided into six themes ‘ Prevalence and statistics’, ‘Red flag’, ‘Natural healing’, ‘Imaging’, ‘Treatment strategies’, and ‘Pain physiology’ . Participants had to rate the extent to which each message increased their confidence using a 5-point Likert scale. Messages were categorized into four levels of perceived confidence based on participants’ responses: high (≥80% rated the message as ‘provide confidence’ or ‘significantly provide confidence’), moderate (60–79%), low (40–59%) and very low (≤40%). Correlation and non-parametric analyses examined the relationships between confidence ratings, demographic variables and personality traits. Results Messages that emphasized patient autonomy and the absence of red flags were perceived as particularly reassuring and received the highest ratings (≥80%). In contrast, messages that referred to natural healing and the neurophysiology of pain were perceived as less effective in providing confidence. Personality traits and background characteristics had minimal effects on perceived reassurance. Conclusions Reassuring communication that emphasizes patient autonomy and the low likelihood of serious pathology can boost confidence in individuals with LBP and may be more impactful than patient-specific characteristics. These findings may help PTs refine their communication strategies and strengthen therapeutic relationships, potentially leading to better treatment outcomes. Future research should explore the implications of these findings in clinical settings in real-life interactions.